Meningeal carcinomatosis following a curative endoscopic submucosal dissection of early gastric cancer: a case report - Yu, Zhengping; Tu, Qi; Wang, Zhenwen; Ding, Ying; Yang, Xueping; Zhu, Liang (Zeitschrift für Gastroenterologie, 2021)
Meningeal carcinomatosis (MC) is reported to occur in 4%–15% of patients with solid tumors. MC is not commonly associated with gastric carcinoma and is extremely rare in patients with early gastric cancer (EGC). MC derived from EGC after curative endoscopic submucosal dissection (ESD) has not been reported before. We present a rare case of a 49-year-old patient who developed MC after curative ESD of EGC. The cancer was an ulcerated lesion approximately 1.0 cm in diameter in endoscopic appearance in the minor curvature of the gastric antrum. The pathological examination after ESD indicated high-grade intraepithelial neoplasia (1.3 × 2.1 cm in size) with localized moderately differentiated adenocarcinoma (0–IIc in tumor stage, intestinal type in Lauren classification), which was confined to the mucosal layer with an intact submucosal layer and muscularis propria. The lesion was removed entirely by curative dissection without vertical and horizontal resection margins involvement in pathology. Two months after ESD, the patient was readmitted for severe headache and vomiting. Cytological examination of the cerebrospinal fluid found malignant tumor cells, which were considered by pathologists to have metastasized from the stomach, further confirming MC derived from EGC. The patient’s condition deteriorated dramatically, which prevented him from receiving further therapies, such as chemotherapy, and he died 3 days after the diagnosis of MC. In conclusion, EGC can cause MC, even after curative ESD. New neurological manifestations in patients with EGC can alert physicians to a diagnosis of MC, and more attention needs to be paid to evaluating the nervous system and establishing diagnostic and therapeutic strategies as soon as possible.
Keywords: meningeale Karzinomatose; Magenkrebs im Frühstadium; endoskopische Submukosadissektion; Gehirn-Rückenmarks-Flüssigkeit; Fallbericht